2022
DOI: 10.1089/aid.2021.0140
|View full text |Cite
|
Sign up to set email alerts
|

Tenofovir, Lamivudine, and Dolutegravir Among Rural Adolescents in Zimbabwe: A Cautionary Tale

Abstract: Tenofovir disoproxil fumarate, lamivudine and dolutegravir (TLD) as a safe and more effective single daily dose regimen is rolling out in Africa for people living with HIV.Although access to viral load (VL) testing is improving, patients may still be transitioned to TLD with virologic failure and potential drug resistance. We reviewed annual VL test results

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 17 publications
3
8
0
Order By: Relevance
“…On the other hand, clinical experience with DTG is growing in Africa and consistent findings from cohort studies among ART-naive and ART-experienced individuals are also being reported in real-world settings [21][22][23][24]. We recently showed that virological suppression increased from 76 to 95% following a switch to TLD among adolescents in rural Zimbabwe [25]. Similarly Brown et al [26] in 2022 showed that virological suppression (viral load <1000 copies/ml) of 99% was achieved at 4 months following the transition to DTG among individuals in Lesotho.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…On the other hand, clinical experience with DTG is growing in Africa and consistent findings from cohort studies among ART-naive and ART-experienced individuals are also being reported in real-world settings [21][22][23][24]. We recently showed that virological suppression increased from 76 to 95% following a switch to TLD among adolescents in rural Zimbabwe [25]. Similarly Brown et al [26] in 2022 showed that virological suppression (viral load <1000 copies/ml) of 99% was achieved at 4 months following the transition to DTG among individuals in Lesotho.…”
Section: Discussionsupporting
confidence: 55%
“…At baseline, participants had a normal BMI with a median (IQR) of 21.9 (19.1-26.0) kg/m 2 and 8% of the participants were obese with BMI at least 30 kg/m 2 . Female individuals had a significant higher median (IQR) BMI compared with male individuals (23 (20)(21)(22)(23)(24)(25)(26)(27) vs. 20 (19)(20)(21)(22)(23)(24), P ¼ 0.009, two-sample Wilcoxon rank-sum test).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Patients who exhibit virological failure and potential medication resistance may still be moved to therapy with TLD despite the growing accessibility of viral load (VL) testing. 23 …”
Section: Discussionmentioning
confidence: 99%
“…Previous Zimbabwe studies show high pretreatment and acquired HIVDR against non-nucleoside reverse transcriptase inhibitors. Dolutegravir is the preferred first-line regimen but enhanced HIVDR surveillance is crucial to preserve its efficacy ( 12 , 21 , 22 ). In this article, we discuss the need, benefits, and strategies for strengthening and enhancing HIVDR surveillance in Zimbabwe.…”
Section: Introductionmentioning
confidence: 99%